THE GOVERNMENT'S PRIORITIZATION OF INFORMATION OVER SANCTION: IMPLICATIONS FOR COMPLIANCE - Martinez, Veronica Root (Law and contemporary problems, 2020)
Who should be responsible for stopping misconduct within organizations?1 One might think it should be the primary responsibility of federal prosecutors to aggressively seek to bring criminal cases against rogue corporations. Or one might look to regulators as those charged with creating a series of checks and balances to ensure that wrongdoing within firms is easy to detect and prevent. Still others might look to the corporations themselves to ensure that their employees are acting within the bounds of legal and regulatory requirements. In reality, each of these three actors—prosecutors, regulators, and the firm itself— are responsible, in different ways, for responding to the misconduct that occurs within corporations. And when they fail, there are often significant consequences. Take, for example, Purdue Pharma. Prosecutors investigated Purdue Pharma in the mid-1990s and determined that it “knew about ‘significant’ abuse of OxyContin in the first years after the drug’s introduction in 1996 and concealed that information.”2 Instead of indicting executives on felony charges, as recommended by the prosecutors investigating the company,3 the Department of Justice (DOJ) decided to pursue less severe enforcement activity and settled the case. Purdue Pharma paid $600 million in fines and other payments, a significant and, at the time, one of the largest sums ever paid.4 The Food and Drug Administration, the regulator overseeing Purdue Pharma, chose not to force the company to reformulate OxyContin in 2001, which would have made the drug more difficult to abuse.5 And Purdue Pharma, on its own, chose not to reformulate OxyContin until 2010, despite the fact that it was allegedly aware that the drug was highly addictive, often abused, and associated with overdoses.6 Unfortunately, the damage was done, and OxyContin wreaked havoc in communities all across the United States. Ultimately, Purdue Pharma entered into a nationwide settlement in 2019, which contemplated the dissolution of the firm,7 and, in 2020, pleaded guilty to criminal charges for opioid sales.8 Yet, it is safe to say that while the harms caused by OxyContin were known for over a decade, the actions taken by prosecutors, regulators, and the firm largely failed to adequately mitigate the damage the drug caused, and continues to cause, to people and communities.9 The question is why? When large scandals are discovered, the firm itself is certainly held to account by the public for its failure to prevent harm, but often the government also finds itself the subject of criticism. Why did regulators not act more aggressively towards Wells Fargo?10 Why did the government not prosecute more individuals for the 2008 financial crisis?11 The critique comes in a variety of forms, but often boils down to questioning why federal prosecutors and regulators are unwilling to enforce laws to the fullest extent possible against corporations who commit corporate misconduct through their employees or agents.12 This Article puts forth a new account to help explain the decision by governmental actors to prioritize the receipt of information from, over the pursuit of high-level sanctions of, corporate offenders.